Thriving after trauma: the experience of parents of murdered children - Parappully, Jose (2002)
Psychological literature on trauma usually focuses on pathology that results from trauma and pays little attention to positive out-comes. This article presents a phenomenological inquiry into the experiences of a profoundly traumatized group of people - parents whose son or daughter has been murdered - to assess if they were able to experience a positive outcome resulting from their trauma and to identify associated processes and resources. Of 65 parents who volunteered, 16 were selected to complete a questionaire and were given in-depth, semistructured interviews. The interview data, analyzed qualitatively, affirms positive outcomes for these parents. Four processes - acceptance, finding meaning, personal decision making, and reaching out to others in compassion - and six resources - personal qualities, spirituality, continuing bond with the victim, social support, previous coping experience, and self-care-facilitate a positive outcome. - Reproduced.
Keywords: Murder victims; Children; Parents